1998
DOI: 10.1007/s004420050580
|View full text |Cite
|
Sign up to set email alerts
|

Do Svalbard reindeer regulate standing crop in the absence of predators?

Abstract: The Svalbard reindeer is the only mammalian herbivore in Adventdalen (78°N), Svalbard, where it has no natural predators. To test if herbivores in the absence of predators regulate standing crop to a level independent of productivity, which is one of the predictions of the "exploitation ecosystems" model, herbivore exclosures were set up in 1992 in Salix heath, Luzula heath, Cassiope heath, and Alopecurus meadow in Adventdalen. Standing crop of vascular plants was harvested and measured inside and outside the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…Since then, there has been a growing body of literature reporting on the impacts and mechanisms by which vertebrate herbivores inXuence arctic ecosystems. Early accounts stressed that herbivore impacts were negligible, as environmental severity was believed to be overwhelmingly great (JeVeries et al 1994;Wegener and Odasz-Albrigtsen 1998). Though perhaps still valid for some of the most extreme areas of the arctic, this view is largely being abandoned as the number of studies reporting on substantial herbivore inXuence is mounting (Srivastava and JeVeries 1996;Adler and Morales 1999;Olofsson 2006; Van der Wal 2006;Bråthen et al 2007;Post and Pedersen 2008).…”
Section: Introductionmentioning
confidence: 95%
“…Since then, there has been a growing body of literature reporting on the impacts and mechanisms by which vertebrate herbivores inXuence arctic ecosystems. Early accounts stressed that herbivore impacts were negligible, as environmental severity was believed to be overwhelmingly great (JeVeries et al 1994;Wegener and Odasz-Albrigtsen 1998). Though perhaps still valid for some of the most extreme areas of the arctic, this view is largely being abandoned as the number of studies reporting on substantial herbivore inXuence is mounting (Srivastava and JeVeries 1996;Adler and Morales 1999;Olofsson 2006; Van der Wal 2006;Bråthen et al 2007;Post and Pedersen 2008).…”
Section: Introductionmentioning
confidence: 95%
“…These bad winters prevent the population from increasing to summer densities that bring carrying capacity problems relating to overgrazing, food competition and reduced body condition. Supporting data come from a controlled grazing experiment in Adventdalen where Wegener & Odasz-Albrigtsen (1998) found that reindeer grazing had no significant effect on the live biomass of vascular plants, woody plants, herbs or graminoids. Body composition data (Reimers 1982b;Reimers et al 1982;Tyler 1987a, b) confirm that during summer Svalbard reindeer rapidly recover from the starvation and greatly reduced body mass that they undergo during the preceding winter.…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to Rangifer subspecies elsewhere, Svalbard reindeer live individually or in small groups (Alendal & Byrkjedal 1976;Alendal et al 1979), are seasonally sedentary (Tyler & Øritsland 1989) and are not nomadic. Their ability to build up fat reserves in times of plenty for use in times of scarcity (Reimers et al 1982) makes them less dependent on the lichens that are easily digestible but are poorly resistant to grazing and trampling; these lichens have been replaced in the Svalbard reindeer's winter diet by far more grazing-resistant vascular plants, woody plants, herbs and graminoids (Hjeljord 1975;Punsvik et al 1980;Staaland 1984;Wegener & Odasz-Albrigtsen 1998).…”
mentioning
confidence: 99%
“…Annual mean precipitation is only 200 mm with most falling as snow in winter and persisting from October to early June. Thus, the growing season for plants is short and productivity low, typically 40-60 g m Ϫ2 (Wegener & Odasz-Albrigtsen 1998). Although Svalbard reindeer do not undertake seasonal migrations, local emigration does take place in severe winter weather (Tyler 1987;Tyler & Øritsland 1989;Aanes et al 2000), presumably because animals search for more accessible forage.…”
Section: (A) Study Area and Reindeer Populationmentioning
confidence: 99%